Genesis of the symbolism concept in the works of Olexandr Oles (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article examines the formation of the artistic and aesthetic conception of Olexander Oles’s symbolism of  the west european tradition.
Keywords: symbolism; context; poetics; symbol; aesthetics